Reassessing the Class Character of Karl Marx and His Economic Theories: A Multi-Perspective Analysis - Poonamand Dr.AshokChauhan (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This paper investigates the class character of Karl Marx, both as a historical figure and as a producer of one of the most influential bodies of economic theory in modern history. While Marx is widely celebrated for his revolutionary critique of capitalism and his commitment to working-class emancipation, this study probes deeper into the apparent paradox between his bourgeois social origins and his proletarian ideological commitments. Drawing from Marxian, Weberian, and Bourdieuan theoretical frameworks, the paper evaluates how Marx’s class background—rooted in the educated, middle-class professional strata—interacted with the political and economic conditions of 19th-century Europe to shape his intellectual evolution.